A Study on the Pronunciation of Consonant: A Case Study of Javanese learners of English - Luthfi Ali, Mukhamad; , Agus Wijayanto, Ph.D; , Muamaroh, Ph.D (2016)
The present research is to investigate the characteristic pronunciation of consonant difficulties encountered by Javanese learners of English. The idea for this study has risen out when the researcher teaching English at one of senior high school in central Java. The researcher often found the lack of systematic of sound system produced by Indonesian EFL learners, especially on consonant sounds. In this research, the researcher used descriptive method, which is appropriate to the research. In collecting the data, the present study applied direct observation. Subject of the research are 20 Javanese learners of English which have gotten the material of English pronunciation. From 21 consonants that studied, the researcher found 12 sound shifts done by JLE, they are; /f/, /tʃ/, /dʒ/, /b/, /g/, /d/, /ʃ/, /θ/, /ð/, /ʒ/, /z/, and /v/. The most difficult sound that found by the researcher was /ʒ/. JLE could only pronounce 9.28% correctly. This phoneme also has 7 sound changes. Most of them change it into /dʒ/ in initial position, /ʃ/ in medial position, and /dʒ/ in final position. The researcher also found that the position of sounds in initial, medial, and final influences the sound shift. Those difficulties appear because of three major problems; the differences in the phonemic systems between English and Javanese, the non-existence of consonant clusters in Javanese, and a systematic deviation. Key words: Pronunciation, Consonants, Sound Shift, Javanese Learners of English